Removal of micropollutants, facultative pathogenic and antibiotic resistant bacteria in a full-scale retention soil filter receiving combined sewer overflow. Issue 1 (5th December 2014) - Scheurer, Marco; Heß, Stefanie; Lüddeke, Frauke; Sacher, Frank; Güde, Hans; Löffler, Herbert; Gallert, Claudia
Abstract : The contamination of surface waters by combined sewer overflow is reduced by retention soil filters. Abstract : Combined sewer systems collect surface runoff as well as wastewater of industrial and domestic origin. During periods of heavy rainfall the capacity of the sewer system is exceeded and the overflow is discharged into receiving waters without any treatment. Consequently, combined sewer overflow (CSO) is considered as a major source of water pollution. This study investigates the effectiveness of a retention soil filter (RSF) for the removal of micropollutants as well as facultative pathogenic and antibiotic resistant bacteria from CSO. The removal of organic group parameters like total organic carbon was excellent and the removal efficiency for micropollutants of the RSF and the wastewater treatment plant (WWTP), which treats wastewater of the same origin during dry and normal weather conditions, was comparable. Compounds of high environmental concern like estrogens or certain pharmaceuticals, e.g. diclofenac, were completely eliminated or removed to a high degree during RSF passage. RSF treatment also reduced the number of E. coli, enterococci and staphylococci by 2.7, 2.2 and 2.4 log-units (median values), respectively. Obviously, some Staphylococcus species can better adapt to the conditions of the RSF than others as a shift of the abundance of the different species was observed when comparing the diversity of staphylococci obtained from the RSF influent and effluent. RSF treatment also decreased the absolute number of antibiotic resistant bacteria. The percentage of antibiotic resistant E. coli and staphylococci isolates also decreased during passage of the RSF, whereas the percentage of resistant enterococci did not change. For E. coli ampicillin and for enterococci and staphylococci erythromycin determined the antibiotic resistance level. The results demonstrate that RSFs can be considered as an adequate treatment option for CSO. The performance for the removal of micropollutants is comparable with a medium sized WWTP with conventional activated sludge treatment. The number of facultative pathogenic and antibiotic resistant bacteria was considerably decreased during RSF passage. However, as RSF effluents still contained antibiotic resistance genes and traces of micropollutants; receiving waters may still be at risk from negative environmental impacts.